Winter lost - Briggs, Patricia (New York Ace, 2024)
"In the supernatural realms, there are creatures who belong to winter. I am not one of them. But like the coyote I can become at will, I am adaptable. My name is Mercy Thompson Hauptman, and my mate, Adam, is the werewolf who leads the Columbia Basin Pack, the pack charged with keeping the people who live and work in the Tri-Cities of Washington State safe. It's a hard job, and it doesn't leave much room for side quests--which is why when I needed to travel to Montana to help my brother, I intended to go by myself. But I'm not alone anymore. Together, Adam and I find ourselves trapped with strangers in a lodge in the heart of the wilderness, in the teeth of a storm of legendary power, only to discover my brother's issues are just part of a problem much bigger than we imagined. Arcane and ancient magics are at work that could, unless we are very careful, bring about the end of the world."--
114097
Keywords: Thompson, Mercy -- (Fictitious character) -- Fiction; Shapeshifting -- Fiction; Werewolves -- Fiction; Coyote -- Fiction; Magic -- Fiction; Paranormal romance stories; Fantasy fiction; Werewolf fiction; Novels; Romans